Enhancement of the Efficiency and Selectivity for Carbon Dioxide Electroreduction to Fuels on Tailored Copper Catalyst Architectures. Issue 8 (1st April 2016) - Bevilacqua, Manuela; Filippi, Jonathan; Folliero, Maria; Lavacchi, Alessandro; Miller, Hamish A.; Marchionni, Andrea; Vizza, Francesco
Abstract: The electroreduction of CO2 is one of the most promising strategies for the production of fuels, energy vectors, and chemicals from CO2 . Recently, we have described the realization of an electrochemical reactor based on the use of a Cu cathode for the CO2 electroreduction reaction. Here, three Cu electrodes were prepared by different techniques that generate different surface structures and morphologies. These three Cu cathodes, employed in the electrolysis cell, are compared in terms of Faradaic efficiency (FE) and product selectivity to a reference Cu foil electrode. The higher active surface area of these samples produced an improved total FE versus the Cu smooth plate. In terms of product selectivity, Cu electroplating onto a Cu foil enhanced HCOOK production strongly; the electrofaceting treatment of the Cu foil drove selectivity towards the production of CH4 . In the third electrode, the deposition of Cu onto carbon cloth favors the formation of C2 H4 . Abstract : Copper chameleon : Three Cu electrodes are prepared by different techniques that generate different surface structures and morphologies. These three Cu cathodes, employed in an electrolysis cell, are compared in terms of Faradaic efficiency and product selectivity to a reference Cu foil electrode.